Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/rheumatology/keab824
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced mitochondrial function through glutamine metabolism in plasmablast differentiation in systemic lupus erythematosus

Abstract: Objective To evaluate the dysfunction of B cell metabolism and its involvement in SLE pathology. Methods We assessed the expression of metabolic markers of B cells in the peripheral blood of healthy controls (HCs) and SLE patients by using flow cytometry. In vitro, peripheral B cells were isolated from HCs and SLE patients to investigate the metabolic regulation mechanisms involved in their differentiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Furthermore, the degree of hyperpolarization correlated with SLEDAI-2K. The authors also noted that glutaminolysis, which generates essential metabolites for OXPHOS, played a key role in the differentiation into plasmablasts ( 31 ).…”
Section: Mitochondrial Dysfunction In Slementioning
confidence: 96%
“…Furthermore, the degree of hyperpolarization correlated with SLEDAI-2K. The authors also noted that glutaminolysis, which generates essential metabolites for OXPHOS, played a key role in the differentiation into plasmablasts ( 31 ).…”
Section: Mitochondrial Dysfunction In Slementioning
confidence: 96%
“…The glutaminase inhibitor BPTES, which is a limited inhibitor of glutamine degradation, decreased DiOc6 expression, oxidative phosphorylation, ROS production, and ATP production, as well as suppressed plasmablast differentiation and antibody production. Metformin inhibited CpG-and IFNαinduced glutamine uptake, as well as suppressed plasmablast differentiation and antibody production (Figure 1) (109). In SLE patients, B-cells are activated and differentiated by viral and autoantigen-derived nucleic acids and IFN-α stimulation through the uptake of amino acids such as methionine and glutamine, which are related to the pathogenesis of SLE.…”
Section: Immunometabolism In the Process Of B-cell Differentiation In...mentioning
confidence: 94%
“…Liu et al showed that BAFF is critical for the survival of anergic B cells, as well as rescuing autoreactive B cells from checkpoint deletion [78][79][80]. Several clinical studies have shown that lupus patients have much higher serum BAFF than healthy individuals, which allows the autoreactive B cells in lupus patients to escape metabolic restriction [81][82][83][84].…”
Section: B-cell-activating Factor and B-cell Survivalmentioning
confidence: 99%
“…In lupus patients, T cells show mitochondrial synthesis and poor mitophagy [80]. Similarity B cells in SLE have larger mitochondria [81]. A study by Sumikawa et al showed that mitochondrial dysfunction in B cells was linked to plasmablast differentiation and disease activity in SLE.…”
Section: Tolerogenicity In B-cell Metabolismmentioning
confidence: 99%
See 1 more Smart Citation